2018
DOI: 10.3390/molecules23040953
|View full text |Cite
|
Sign up to set email alerts
|

Search for Partner Proteins of A. thaliana Immunophilins Involved in the Control of Plant Immunity

Abstract: The involvement of plant immunophilins in multiple essential processes such as development, various ways of adapting to biotic and abiotic stresses, and photosynthesis has already been established. Previously, research has demonstrated the involvement of three immunophilin genes (AtCYP19-1/ROC3, AtFKBP65/ROF2, and AtCYP57) in the control of plant response to invasion by various pathogens. Current research attempts to identify host target proteins for each of the selected immunophilins. As a result, candidate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…With respect to the interaction of AtNHR2A and AtNHR2B with proteins known to be important in regulation of plant immunity, we found that AtNHR2A interacted with AtPRL1, a protein that interacts with the plant defense transcription factor AtCDC5 (Palma et al, 2007), with the MAP kinase AtMPK11 (Carrasco et al, 2014), and with AtENGD-1 (Cheung et al, 2010). AtENGD-1 is a GTP-binding protein that participates in plant immunity regulating the production of ROS and interacting with the immunophilin AtCYP19, which is also important for plant defense responses against P. syringae (Cheung et al, 2010;Pogorelko et al, 2014;Abdeeva et al, 2018). We successfully validated the interaction between AtNHR2A and AtENGD-1 by semi-in vivo co-immunoprecipitation wherein His-AtENGD-1 purified from bacteria was successfully co-immunoprecipitated by AtNHR2A-GFP expressed and purified from N. benthamiana.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…With respect to the interaction of AtNHR2A and AtNHR2B with proteins known to be important in regulation of plant immunity, we found that AtNHR2A interacted with AtPRL1, a protein that interacts with the plant defense transcription factor AtCDC5 (Palma et al, 2007), with the MAP kinase AtMPK11 (Carrasco et al, 2014), and with AtENGD-1 (Cheung et al, 2010). AtENGD-1 is a GTP-binding protein that participates in plant immunity regulating the production of ROS and interacting with the immunophilin AtCYP19, which is also important for plant defense responses against P. syringae (Cheung et al, 2010;Pogorelko et al, 2014;Abdeeva et al, 2018). We successfully validated the interaction between AtNHR2A and AtENGD-1 by semi-in vivo co-immunoprecipitation wherein His-AtENGD-1 purified from bacteria was successfully co-immunoprecipitated by AtNHR2A-GFP expressed and purified from N. benthamiana.…”
Section: Discussionmentioning
confidence: 80%
“…To further confirm the accuracy of the IP-MS method, and to gain insight into the function of AtNHR2A and AtNHR2B in plant immunity, we chose to validate the interaction between AtNHR2A or AtNHR2B with proteins known to function in plant innate immunity such as AtENGD-1, AtRPN1A, and AtCCoAMT1 (Yao et al, 2012;Abdeeva et al, 2018;Xie et al, 2018). AtENGD-1 was fused to the 6× histidine (6× His) tag and expressed and purified from E. coli.…”
Section: Validation Of Selected Interaction Pairs By Co-immunoprecipimentioning
confidence: 99%
“…According to TAIR, the genome of Arabidopsis thaliana contains 27,416 protein-coding genes ( Table S3 ). The main portion of PPIs was identified in several databases, while an additional 920 PPIs were identified through a PubMed search for studies of interactions in Arabidopsis published over the last twenty years [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , …”
Section: Resultsmentioning
confidence: 99%
“…The major functions of cyclophilin are as foldase, scaffold and chaperon, and in deed CYP imparts on its target protein stability and activity, which participates in plant growth, abiotic and biotic stress response (Zhu, ; Fu et al , ; Pogorelko et al , ; Abdeeva et al , ). To further reveal the relationships between OsCYP20‐2 and OsFSD2, we performed a Y3H assay and showed that OsCYP20‐2 promoted OsFSD2 forming homodimers (Fig.…”
Section: Resultsmentioning
confidence: 99%